Ruthenium‐Containing Linear Helicates and Mesocates with Tuneable p53‐Selective Cytotoxicity in Colorectal Cancer Cells - Allison, Simon J.; Cooke, David; Davidson, Francesca S.; Elliott, Paul I. P.; Faulkner, Robert A.; Griffiths, Hollie B. S.; Harper, Owen J.; Hussain, Omar; Owen‐Lynch, P. Jane; Phillips, Roger M.; Rice, Craig R.; Shepherd, Samantha L.; et al. (Angewandte Chemie International Edition, 2018)
The ligands L1 and L2 both form separable dinuclear double‐stranded helicate and mesocate complexes with RuII. In contrast to clinically approved platinates, the helicate isomer of [Ru2(L1)2]4+ was preferentially cytotoxic to isogenic cells (HCT116 p53−/−), which lack the critical tumour suppressor gene. The mesocate isomer shows the reverse selectivity, with the achiral isomer being preferentially cytotoxic towards HCT116 p53+/+. Other structurally similar RuII‐containing dinuclear complexes showed very little cytotoxic activity. This study demonstrates that alterations in ligand or isomer can have profound effects on cytotoxicity towards cancer cells of different p53 status and suggests that selectivity can be “tuned” to either genotype. In the search for compounds that can target difficult‐to‐treat tumours that lack the p53 tumour suppressor gene, [Ru2(L1)2]4+ is a promising compound for further development. Cell‐selective: The bis‐tridentate ligand L1 forms both the dinuclear double helicate and mesocate upon reaction with ruthenium(II). Cytotoxicity studies show that the helicate is selective to HCT116 p53−/− cancer cells whereas the mesocate is selective to HCT116 p53+/+.